Clinical parameters affecting multipotent adult progenitor cells in vitro. Issue 10 (October 2019) - Jackson, Margaret L.; Ruppert, Katherine A.; Kota, Daniel J.; Prabhakara, Karthik S.; Hetz, Robert A.; Aertker, Benjamin M.; Bedi, Supinder; Mays, Robert W.; Olson, Scott D.; Cox, Charles S.
Abstract: Background: Human multipotent adult progenitor cells (MAPC®) are an emerging therapy for traumatic brain injury (TBI); however, clinically translating a therapy involves overcoming many factors in vivo which are not present in pre-clinical testing. In this study we examined clinical parameters in vitro that may impact cell therapy efficacy. Methods: MAPC were infused through varying gauged needles and catheters with and without chlorhexidine, and their viability tested with trypan blue exclusion. MAPC were co-cultured with phenytoin and celecoxib at relevant clinical concentrations for 1 h and 24 h. Anti-inflammatory potency was tested using a stimulated rat splenocyte co-culture and ELISA for TNF-α production. MAPC were cultured under different osmolar concentrations and stained with propidium iodide for viability. Anti-inflammatory potency was tested by co-culture of MAPC with naïve lymphocytes activated by CD3/CD28 beads, and Click-iT® Plus EdU was used to quantify proliferation by flow cytometry. Results: The mean viability of the MAPC infused via needles was 95 ± 1%; no difference was seen with varying flow rate, but viability was notably reduced by chlorhexidine. MAPC function was not impaired by co-culture with phenytoin, celecoxib, or combination with both. Co-culture with phenytoin showed a decrease in TNF-α production as compared to the MAPC control. MAPC cultured at varying osmolar concentrations all had viabilities greater than 90% with no statistical difference between them. Co-culture of MAPC with CD3/CD28 activated PBMCs showed a significant reduction in proliferation as measured by EdU uptake. Discussion: Needle diameter, phenytoin, celecoxib, and a relevant range of osmolarities do not impair MAPC viability or anti-inflammatory potency in vitro .